TRANSACTION THEORY, FORMS AND METHODS OF CORPORATE MANAGEMENT, COSTS OF INTRA-FIRM COORDINATION, PLANNING AND EXCHANGE - S. V. Bel'chenko; D. A. Maksimov (Модернизация, инновация, развитие, 2016)
Business activity managerial structure improvements and developments after transition to market economy are discussed on the basis of the production costs minimization and inner company coordination and exchange concept. Substantiation is given to most widespread forms of cooperative property, to cooperative management development trends as well as to their relation to the scope of internal transaction costs of the company.